The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/ci-12-2018-0097
|View full text |Cite
|
Sign up to set email alerts
|

A global taxonomic review and analysis of the development of BIM research between 2006 and 2017

Abstract: Purpose This paper aims to review the status of development of building information modelling (BIM), its trends and themes across the six continents of the world. Design/methodology/approach A total of 914 journal articles sought from the search engine of Web of Science (WOS) based on the country/region option of the WOS to group them into continents. A best-fit approach was then applied in selecting the suitable software programmes for the scientometric analysis and comparisons and deductions were made. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 66 publications
(131 reference statements)
3
42
0
Order By: Relevance
“…Despite the low number of respondents in these studies, it tends to portray the level of awareness in these countries. The high number of BIM publications from Egypt, Nigeria, and South Africa equally matches the high level of awareness in in these countries [62]. However, the level of awareness does not imply the level of implementation.…”
Section: Bim Awareness In Africamentioning
confidence: 73%
See 4 more Smart Citations
“…Despite the low number of respondents in these studies, it tends to portray the level of awareness in these countries. The high number of BIM publications from Egypt, Nigeria, and South Africa equally matches the high level of awareness in in these countries [62]. However, the level of awareness does not imply the level of implementation.…”
Section: Bim Awareness In Africamentioning
confidence: 73%
“…It also revealed that Africa, South America, and the Middle East are lagging, whilst North America, Europe, Asia, and Australia are clearly ahead in BIM adoption. This is supported by the global taxonomic review of BIM by Saka and Chan [62]. Gu and London [50] corroborated this by asserting that BIM development varies from country to country, discipline to discipline, and client to client.…”
Section: Background Of Studymentioning
confidence: 83%
See 3 more Smart Citations